Acute bacterial endophthalmitis after scleral buckling surgery with chandelier endoillumination - Takato Sakono; Hiroki Otsuka; Hideki Shiihara; Naoya Yoshihara; Taiji Sakamoto (American Journal of Ophthalmology Case Reports, 2017)
Purpose: The non-contact wide-angle viewing system (WAVS) with chandelier endoillumination is being used more commonly during scleral buckling surgery for rhegmatogenous retinal detachments although its safety has not been established. We report our findings in a case of bacterial endophthalmitis that developed after scleral buckling surgery with WAVS and chandelier endoillumination. Observations: A 42-year-old man underwent scleral buckling surgery for a rhegmatogenous retinal detachment in his right eye using a WAVS with chandelier endoillumination. Three days after the surgery, the patient noticed a marked decrease in his vision with ocular pain. Slit-lamp examination showed dense infiltration in the anterior chamber and vitreous body. Pars plana vitrectomy with antibiotic irrigation was done immediately, and Staphylococcus epidermidis was detected in the vitreous fluid. After vancomycin 6/day for 4 weeks, the inflammation gradually subsided, and the visual acuity recovered to 20/20 in 3 months. Conclusions and importance: Acute bacterial endophthalmitis can develop after scleral buckling surgery performed with WAVS and chandelier endoillumination.